2015
DOI: 10.1515/aoa-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of a Step Change in Piezo Actuator Structure on Vibration Reduction Level in Plates

Abstract: This paper presents numerical analyses and a physical experiment on efficiency of different shapes and material composition of piezo actuators on vibration reduction. For this purpose numerical models of a plate clamped on all sides with piezo actuators attached were developed. The elements used were either standard homogeneous elements or the proposed two-part elements with different material composition for inner and outer part of piezo ceramic. Numerical analyses were performed using ANSYS software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The plate model is actually the same as in [12,14] that is a steel plate (400 mm × 400 mm × 2 mm) with 2 piezo elements attached. One of these elements is a homogeneous square-based element placed near the centre of the plate with area of 1600 mm 2 and height of 1 mm used to excite vibration of the plate.…”
Section: Numerical Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plate model is actually the same as in [12,14] that is a steel plate (400 mm × 400 mm × 2 mm) with 2 piezo elements attached. One of these elements is a homogeneous square-based element placed near the centre of the plate with area of 1600 mm 2 and height of 1 mm used to excite vibration of the plate.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…The next step was testing if the placement of the inner part of a two-part element had an effect on its effectiveness [13]. Another publication [14] expanded on numerical models and presented early results of physical experiment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These works generally concluded that the introduced change in material properties of piezo actuators did not produce any substantial change in the levels of reduction of plates vibration. Another work presented the attempts to verify numerical results with physical experiment (Wiciak and Trojanowski, 2015b). Unfortunately, a small number of samples (they had to be custom made) and differences between said samples made the results unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%